1999
DOI: 10.1016/s0092-8674(00)81968-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the DNA Repair Enzyme Endonuclease IV and Its DNA Complex

Abstract: Endonuclease IV is the archetype for a conserved apurinic/apyrimidinic (AP) endonuclease family that primes DNA repair synthesis by cleaving the DNA backbone 5' of AP sites. The crystal structures of Endonuclease IV and its AP-DNA complex at 1.02 and 1.55 A resolution reveal how an alpha8beta8 TIM barrel fold can bind dsDNA. Enzyme loops intercalate side chains at the abasic site, compress the DNA backbone, bend the DNA approximately 90 degrees, and promote double-nucleotide flipping to sequester the extraheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
189
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(196 citation statements)
references
References 58 publications
7
189
0
Order By: Relevance
“…Indeed, we have shown that truncated Ape1 (N⌬61-Ape1) lacking the first 61 N-terminal amino acids has reduced NIR but normal AP endonuclease activity (3). The crystal structure of Nfo complexed to duplex DNA containing an AP site shows that three Zn 2ϩ ions are bound in the protein by conserved residues that cluster at the center of a crescent-shaped cavity (6). Site-directed mutagenesis of the con- Nfo-H69A Nfo-G149D served amino acid residues support participation of Zn 2ϩ ions in catalysis of phosphodiester bond cleavage (18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we have shown that truncated Ape1 (N⌬61-Ape1) lacking the first 61 N-terminal amino acids has reduced NIR but normal AP endonuclease activity (3). The crystal structure of Nfo complexed to duplex DNA containing an AP site shows that three Zn 2ϩ ions are bound in the protein by conserved residues that cluster at the center of a crescent-shaped cavity (6). Site-directed mutagenesis of the con- Nfo-H69A Nfo-G149D served amino acid residues support participation of Zn 2ϩ ions in catalysis of phosphodiester bond cleavage (18).…”
Section: Resultsmentioning
confidence: 99%
“…Nfo is an EDTA-resistant multifunctional enzyme with AP endonuclease, 3Ј-phosphatase and 3Ј-phosphoglycoaldehyde diesterase activities (4). The protein contains three Zn 2ϩ ions in the active site that are critical for its functions (5,6). The nfo gene is under the control of the soxRS system and inducible by O 2 Ϫ and NO⅐ radicals (7).…”
mentioning
confidence: 99%
“…Several groups of crystallographers have revealed the structures of DNA protein complexes with the base flipping (31)(32)(33)(34)(35)(36)(37)(38). However, in the case of the CPD photolyase, no structural evidence of CPD-flipping has been shown.…”
Section: Table II Analyses Of the Interactions Between The Cpd Photolmentioning
confidence: 99%
“…5D). Following incision, Ape1 and endonuclease IV both remain tightly bound to their abasic DNA products (35,45), so these two proteins may inhibit DNA synthesis by pol ␤ using a similar mechanism. However, the substrate-specific inhibition of pol ␤ by Ape1, and the apparent lack of specificity of endonuclease IV, may reflect different modes of binding employed by these two enzymes (14).…”
Section: Concentration-dependent Inhibition Of Pol ␤ By Ape1 and E Cmentioning
confidence: 99%
“…However, the substrate-specific inhibition of pol ␤ by Ape1, and the apparent lack of specificity of endonuclease IV, may reflect different modes of binding employed by these two enzymes (14). Both proteins induce DNA bends, but Ape1 induces a relatively mild 35°bend compared with the 90°kink caused by endonuclease IV (45,46). Table I for sequence), 1 nM pol ␤, 20 M dCTP, and either no added Ape1 (filled squares), 50 nM wild-type Ape1 (filled circles), or 50 nM D283A/D308A mutant form of Ape1 (filled triangles).…”
Section: Concentration-dependent Inhibition Of Pol ␤ By Ape1 and E Cmentioning
confidence: 99%